Asesmen Penerapan Green Building Pada Proyek Pembangunan Pasar Raya Kota Padang - Imani, Rafki; Nasmirayanti, Rita; Arman, Utami Dewi; Afrilda Sari (Universitas Andalas, 2025)
Pasar Raya Padang is a major shopping center in Padang City that plays a significant role in the local economy. The application of the Green Building concept in this project not only aims to have a positive impact on the environment, but also to improve the welfare of the surrounding community by providing a healthier and more sustainable environment. This study aims to analyze the dominant and lowest factors in the implementation of Green Building and evaluate the assessment criteria used. The research method includes field surveys and interviews with various related parties, then an assessment is carried out based on the Green Building Council Indonesia (GBCI) standards. Based on the research results, the Pasar Raya Padang project successfully achieved 39.9% of the total Green Building indicators and received a bronze predicate with a percentage of 35%. The dominant factor in the implementation of Green Building in this project is